Production of anti-tetanus toxin IgY and study of its protective effects in a mouse model. Issue 3 (4th May 2023) - Mohammadi, Mohammad; Zangooei, Mohammad; Abbasi, Ebrahim; Ebrahimi Fana, Saeed; Aminian, Mahdi
ABSTRACT: Tetanus is an acute and often fatal infectious disease caused by Clostridium tetani . Tetanus toxin (TT) is responsible for spastic paralysis observed in tetanus. Anti-tetanus antibodies obtained from horses and humans are the most antitoxins used for tetanus treatment, although some clinical side effects and disadvantages have been reported in their application. The aim of this study is the production of anti-TT IgY and evaluation of its protective effects in a mouse model. Anti-TT IgY was purified from the egg yolk using PEG6000 precipitation and water dilution methods, and its purity was verified by SDS-PAGE. Finally, the potency of purified anti-TT IgY in neutralizing the lethal effects of TT was studied in vivo using a mouse model. PEG6000 precipitation method had better results. Animal studies showed that the purified IgY neutralized the toxic effects of 100 MLD of TT and multiple intravenous-dose injections of anti-TT IgY also had a continuous effect of TT neutralization. The purified anti-TT IgY was effective in neutralizing the lethal activity of TT in a mouse model. Our results suggested that IgY could be an alternative therapeutic source for the management of tetanus in the future. Abbreviations Anti-TT, Anti-tetanus toxin; ELISA, Enzyme-linked immunosorbent assay; IgY, Immunoglobulin Y; MLD, Minimum lethal dose; PBS, Phosphate buffer solution; PEG, Polyethylene glycol; SDS-PAGE, Sodium dodecyl sulfate polyacrylamide gel electrophoresis; TIG, Tetanus immune globulin; TT, Tetanus toxin; WD, Water dilution; RT, Room temperature.